Talent identification among female soccer players to national youth teams and player selection to a-national team - Rafoss, K.; Welde, B. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Introduction: The Norwegian Soccer Association has since 1986 identified female players to national youth teams. Youth sports commonly divide participants according to chronological age, based on specific cut-off dates, to establish eligibility for inclusion. The majority of research has examined males and, therefore, the aim of this study was first to study whether an effect of birth-date exists among Norwegian female talented soccer players and, second, to analyse the selection process to sift out players for A-national engagements. Methods: 261 female soccer players selected to the youngest national team in the years 1988 - 2005 constituted our sample. The samples of youth selections were U-16 for the period 1988 -1997 and U-17 for the period 1998 - 2005. A Chi-square test was carried out to check for the existence of relative age effect in the youth teams. Cox regression analysis was applied to evaluate time to event. The event was defined as being selected to the women`s A-national team. Time to event was defined as years elapsed from the first U-16 or U-17 appearance to the first appearance on the women`s A-national team. Date of birth, provincial belonging, if the player had been selected for more than one of the national youth teams, as well as if the player had been selected for the U-21 national team, was chosen as covariates in the Cox regression. Results: 24.9% of the subjects experienced the event.The results showed an over-representation of players born in the first quarter of the selection year in the U-16 and U-17 categories (÷23 = 12.60, P = 0.006). The results from the Cox regression analysis (Wald ÷28 = 45.00, P < 0.004) showed that being selected for the U-21 national team (â = 1.39, P < 0.004), as well as provincial belonging, significantly predicted time to event. Players born in the Western (â = 1.78, P = 0.02) and Eastern (â = 1.50, P = 0.04) part of Norway had significantly diminished time to event as compared to Oslo. Date of birth (â = 0.10, P = 0.68) and being selected for more than one of the youths national team (â = 0.12, P = 0.68) did not significantly impact time to event. Discussion: This study demonstrates an effect of early birth-date upon selection to the youth teams. However, there was no effect of birth-date upon selection to the women`s A-national team. This finding, together with no effect of being selected for more than one of the youths national team, may indicate that selections early in the teens is of minor importance in predicting performance at adulthood. The diminished time to event for players being selected for the U-21 national team, may indicate that identification of future A-national team players are more valid as players approach adult age.